Optimalisasi Kesehatan Prakonsepsi melalui Edukasi Praktik Perawatan Prakonsepsi dan Faktor-Faktornya - Maretta, Megayana Yessy; Wijayanti, Wijayanti; Ma’rifah, Bahriyatul; Andhikatias, Yunia Renny; Apriani, Arista; Blegur, Leny (Jurnal Pemberdayaan Umat, 2026)
Purpose: This community service activity aims to provide information to Women of Childbearing Age (WCA) about preconception care practices and the factors that influence them so they can optimise their preconception health. Methodology: This community service activity was conducted with students from Universitas Kusuma Husada Surakarta in Indonesia and students from the Instituto Ciência da Saúde (ICS) in Timor Leste. The activity was conducted via video conference in the form of a webinar accompanied by a question-and-answer session. Participants were given questionnaires before and after the webinar to measure their knowledge of preconception care practices and the factors that influence them. Results: The activity's results showed a 100.15% increase in knowledge of preconception care, with a p-value of 0.000. Conclusions: Community service activities in the form of providing education on preconception care practices and the factors that influence them are known to be effective in improving individuals' knowledge about preconception care. Limitations: This community service activity was conducted in the form of a webinar, so it was highly dependent on signal stability and there were limitations in the evaluation because it was conducted online. Contributions: This community service activity can motivate WCA to optimise their preconception health by increasing their knowledge about preconception care practices and the factors that influence them.